Load-Deflection Relationship of White Hollow Core reinforced Concrete Panels under Static Load - Saleh, Rafal Mahdi; Khalaf Jarallah, Husain; Salman, Mohammed Mosleh (Engineering, Technology & Applied Science Research, 2025)
The main objective of this research is to examine the load-deflection behavior of White Concrete-Hollow Core Slab (WC-HCS) panels, which were made using white cement, crushed Limestone (LS) as sand, and coarse LS aggregate. The panels were subjected to symmetrical two-point static loads and the results were compared with Normal Concrete-Hollow Core Slab (NC-HCS) panels, which were made utilizing cement, sand, and gravel. The flexural response of steel-reinforced Hollow Core Slab (HCS) was also evaluated. The experimental study involved casting 12 HCS specimens. Each slab had dimensions of 1000 mm length and 450 mm width, with varying thicknesses of 80 mm, 100 mm, and 120 mm. All slabs featured a constant hollow diameter of 32 mm. The slabs were divided into four groups based on three variables: slab thickness, steel reinforcement ratio, and concrete type, namely White Concrete (WC) or Normal Concrete (NC). Concrete mechanical properties, including compressive strength, splitting tensile strength, modulus of rupture, and modulus of elasticity, were studied. Non-destructive testing was performed using Ultrasonic Pulse Velocity (UPV) to assess the concrete quality. The results showed that, for the slabs with varying thickness but the same reinforcement ratio, the deflection decreased by 16.8%, 63.77%, 63.44%, 3.18%, and 57.7%. For NC-HCS slabs, deflection reductions of 23.4% and 47.9% were observed. When varying the reinforcement ratio while maintaining the same slab thickness, the deflection in WC-HCS slabs decreased by 53.5% at 80 mm thickness and by 4.6% at 100 mm thickness, whereas it increased by 18.8% at the same thickness. At 120 mm thickness, the deflection increased by 17.3% and then decreased by 38.3%. The study also explored the effect of concrete type. For slabs with 80 mm thickness, the deflection increased by 48% in WC-HCS compared to NC-HCS. At 100 mm thickness, the deflection decreased by 29.7%, while at 120 mm, it increased by 5.8%.